A new direction for tackling phosphorus inefficiency in the UK food system. (15th July 2022) - Rothwell, S.A.; Forber, K.J.; Dawson, C.J.; Salter, J.L.; Dils, R.M.; Webber, H.; Maguire, J.; Doody, D.G.; Withers, P.J.A.
Abstract: The UK food system is reliant on imported phosphorus (P) to meet food production demand, though inefficient use and poor stewardship means P is currently accumulating in agricultural soils, wasted or lost with detrimental impacts on aquatic environments. This study presents the results of a detailed P Substance Flow Analysis for the UK food system in 2018, developed in collaboration with industry and government, with the key objective of highlighting priority areas for system interventions to improve the sustainability and resilience of P use in the UK food system. In 2018 the UK food system imported 174.6 Gg P, producing food and exportable commodities containing 74.3 Gg P, a P efficiency of only 43%. Three key system hotspots for P inefficiency were identified: Agricultural soil surplus and accumulation (89.2 Gg P), loss to aquatic environments (26.2 Gg P), and waste disposal to landfill and construction (21.8 Gg P). Greatest soil P accumulation occurred in grassland agriculture (85% of total accumulation), driven by loadings of livestock manures. Waste water treatment (12.5 Gg P) and agriculture (8.38 Gg P) account for most P lost to water, and incineration ashes from food system waste (20.3 Gg P) accounted for nearly all P lost to landfill and construction. New strategies and policy to improve the handling and recovery of P from manures, biosolids and food system waste are therefore necessary to improve system P efficiency and reduce P accumulation and losses, though critically, only if they effectively replace imported mineral P fertilisers. Highlights: Only 43% of imported UK food system phosphorus is converted into food and exportable commodities. Manure P is a key driver of system surplus and inefficiency. New policy to support a circular P economy is required.